Elena Evgenievna Koroleva (June 21, 1951 – April 20, 2021) - Kachinskaya, Irina; Rovnova, Olga (Slavistica Vilnensis, 2021)
Jelena Koroliova, Daugavpils University Professor, Dialectologist, since 2008. member of the Old Slavic Research Commission of the International Slavic Committee, wrote articles on lexicoraphy, ethnolinguistics, phraseology, and folklore. She has published a unique work - two volumes of Latgale Old Believers' dialects (2017, 2020), which reflect the spiritual culture of the Old Believers.
Keywords: Elena Koroliova; dialectology; Latgale Old Believers' dialects; Daugavpils university